A rapid gender impact assessment of Australian university responses to COVID-19. Issue 6 (19th September 2022) - Sutherland, Georgina; Vazquez Corona, Martha; Bohren, Meghan; King, Tania; Moosad, Lila; Maheen, Humaira; Scovelle, Anna; Vaughan, Cathy
ABSTRACT: In March 2020, the Australian government introduced a raft of public health initiatives to curb the rising cases of coronavirus disease 2019 (COVID-19) including closing schools and work from home orders. As a group of female academics, we were immediately attuned to the potential of COVID-19 to dilute progress made towards reducing the academic gender gap. This study emerged in response and comprised a rapid gender impact assessment of Australian universities' organisational responses to COVID-19. Our aim was to understand the nature of university policy responses and the extent to which they considered differential impacts for men and women. We searched for relevant communications pertaining to COVID-19 policies from all Australian universities published up to June 2020. Our final sample comprised 79 documents from 29 universities. Information collected was in relation to five key policy domains: support for higher degree research students, leave arrangements for staff, working remotely, managing staff and academic promotion. Overall, little attention was paid to how gender might impact on the need for, or access to, policies in response to COVID-19. Findings showed a reliance on existing workplace mechanisms including access to leave and flexible working arrangements. While the ability to work flexibly is considered a key enabler of gender equality, these approaches have been in place at Australian universities for decades but have, on their own, been inadequate to redress entrenched inequalities. While there is potential for social disruptions brought about by the pandemic to act as a catalyst for change, this will not happen without policies that are transformative in their approach to equality and inclusion.